2010
DOI: 10.3354/meps08643
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the dynamics in benthic structures: environmental effects on morphology in the macroalgal genera Halimeda and Dictyota

Abstract: Macroalgae are modular organisms that can express different morphologies depending on the environment to which they are exposed. Their growth under varying light, temperature, and nutrient regimes, interacting with disturbance factors such as herbivory and hydrodynamics, leads to particular morphological types. The present study illustrates the potential of using morphological variations of benthic modular and/or clonal organisms as indicators of the factors and processes influencing them in their particular l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…Several studies also illustrated that variation of the segments is related to various environmental factors within the marine sublittoral habitats [ 17 – 19 ]. It has been shown that the size of Halimeda segments is often negatively correlated with high irradiation levels typical for shallow habitats close to the sea surface [ 20 , 21 ]. This may lead to large individuals comprising relatively high number of large segments growing in less irradiated, deeper parts of the sublittoral.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies also illustrated that variation of the segments is related to various environmental factors within the marine sublittoral habitats [ 17 – 19 ]. It has been shown that the size of Halimeda segments is often negatively correlated with high irradiation levels typical for shallow habitats close to the sea surface [ 20 , 21 ]. This may lead to large individuals comprising relatively high number of large segments growing in less irradiated, deeper parts of the sublittoral.…”
Section: Introductionmentioning
confidence: 99%
“…This may lead to large individuals comprising relatively high number of large segments growing in less irradiated, deeper parts of the sublittoral. Conversely, photoinhibition, which occurs in Halimeda populations growing in shallow and highly irradiated locations in the upper sublittoral [ 22 , 23 ], may be coupled with relatively small plants characterized by a compact habitus and small segments [ 17 , 21 ]. These small segments of highly irradiated populations have also been reported as being relatively less calcified than those of populations thriving in shaded habitats [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The populations in low light levels have loose thalli, small segments and tri-partite segments (Kooistra & Verbruggen 2005). H. opuntia segments from the inshore patch reefs were large, and the thallus form was more upright than that in the population from the offshore spur and groove area (Yñiguez et al 2010). Additionally, in other species, such as H. macroloba, thallus and segment sizes are large in subtidal zones and low light intensity conditions (Pongparadon et al 2015).…”
Section: Ecological Factors and Their Morphological Plasticity And Admentioning
confidence: 99%
“…The relatively passive role that algae are assumed to play in colonising corals contrasts with their high morphological plasticity in biological interactions. Algal morphology is modified as a response to physical, chemical, and biological factors 8 9 10 11 12 . It has also been suggested that algal phenotypic plasticity may be a key mechanism involved in the occupation of different ecological niches 13 and in the invasion of species 14 , as observed in terrestrial clonal plants.…”
mentioning
confidence: 99%